Association Between Maternal Exposure to SO2 and Congenital Ear Malformations in Offspring: A Population-Based Case-Control Study in Liaoning Province, China - Wei-Jun Yu; Wei-Jun Yu; Na Li; Ting-Ting Gong; Jia-Yu Zhang; Yu-Ting Jiang; Yu-Hong Zhao; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; et al. (Frontiers Media S.A., 2022)
Objectives: To examine associations between maternal sulfur dioxide (SO2) exposure and congenital ear malformations risk in offspring.Methods: We surveyed 1676 cases with congenital ear malformations and 7950 controls from the Maternal and Child Health Certificate Registry of Liaoning Province between 2010 and 2015. SO2 concentrations were obtained from the Municipal Environment Protection Bureau of Liaoning Province. Multivariable logistic regression models and Restricted cubic splines (RCS) model were used to assess the aforementioned association.Results: There were significant associations between maternal SO2 exposure and congenital ear malformations risk during the 3 months before conception (OR Q4 vs. Q1 = 1.93, 95% CI = 1.43-2.59) and the 3 months after conception (OR Q4 vs. Q1 = 1.63, 95% CI = 1.22-2.18). Similar results were obtained in the analysis of single-month exposure windows, except for the third month before conception and the third month after conception. Moreover, these findings were broadly consistent across subgroups and robust in sensitivity analyses. There were non-linear dose-response associations between SO2 exposure and congenital ear malformations based on restricted cubic spline model analysis.Conclusion: Maternal SO2 exposure is associated with increased congenital ear malformations risk in offspring.